Faunist Analysis of Phytonematodes of Corn Plant in The Southern Territory of Surkhandara Region (Texas Journal of Agriculture and Biological Sciences, 2021)
In the southern parts of Surkhandarya region, a comprehensive study of the complex of nematode fauna of grain crops, including corn, and the identification of disease-causing species, the fight against parasitic species in increasing the yield of corn the basis of these data measure is the development of measures